Treatment Persistence of Paliperidone Palmitate 3‐Month in Patients With Schizophrenia: A Japan Medical Data Center Claims Database Analysis - Akihide Wakamatsu; Madoka Chinen; Hiroshi Horio; Chih‐Lin Chiang; Natsuko Tokushige; Yosuke Saga (Neuropsychopharmacology Reports, 2025)
ABSTRACT Aim To examine treatment persistence rates of paliperidone palmitate 3‐month (PP3M) for schizophrenia in Japan because evidence in real‐world settings is limited. Methods A retrospective population‐based cohort study was conducted using the Japan Medical Data Center claims database. The overall cohort comprised schizophrenia patients aged ≥ 18 years, who received paliperidone palmitate 1‐month (PP1M) within 180 days before initiating PP3M. Of patients in the overall cohort, those who received PP1M ≥ 4 times within 180 days at 21–42‐day intervals with the same dosage strength as the last two PP1M doses before switching to PP3M initiated PP3M with a dose equivalent to 3.5‐fold the last PP1M dose and took no other concomitant antipsychotics within 112 days before initiating PP3M were included in the per protocol cohort (PPC). The Kaplan–Meier method was used to calculate PP3M persistence rates in the overall cohort and PP3M monotherapy persistence rates in the PPC. Results In the overall cohort and PPC, 121 patients and 87 patients, with a mean age of 41.5 years and 48%–53% being employed, were followed up for ≤ 27 months. At 365 days and 730 days, the PP3M persistence rate was 76.9% and 71.7% in the overall cohort, and that for PP3M monotherapy was 73.1% and 64.6% in the PPC. Conclusion Treatment persistence rates for PP3M in Japan were relatively high among schizophrenia patients transitioned from PP1M. High persistence rates can be achieved with PP3M monotherapy in patients who have been sufficiently stabilized with PP1M monotherapy prior to initiating PP3M.